2023
DOI: 10.1021/jasms.2c00281
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hybrid Quadrupole-Multireflecting Time-of-Flight Mass Spectrometry System

Abstract: A novel mass spectrometry system is described here comprising a quadrupole-multireflecting time-of-flight design. The new multireflecting time-of-flight analyzer has an effective path length of 48 m and employs planar, gridless ion mirrors providing fourth-order energy focusing resulting in resolving power over 200 000 fwhm and sub-ppm mass accuracy. We show how these attributes are maintained with relatively fast acquisition speeds, setting the system apart from other high resolution mass spectrometers. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…However, in the case of nonisochronism (κ ≠ 0), the addition to the time of flight is determined, as in case 1, by the effective displacement Δx virt . The condition for comparison with ideal pulse remains the same as before (7), but now we need to calculate the velocity gain after all field variations. Here da represents the overshoot addition to the established acceleration a 0 .…”
Section: ■ Analytical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of nonisochronism (κ ≠ 0), the addition to the time of flight is determined, as in case 1, by the effective displacement Δx virt . The condition for comparison with ideal pulse remains the same as before (7), but now we need to calculate the velocity gain after all field variations. Here da represents the overshoot addition to the established acceleration a 0 .…”
Section: ■ Analytical Modelingmentioning
confidence: 99%
“…Modern high-resolution ToF MS instruments have advanced to detect a record number of mass spectra per second, achieving high mass resolution and sub parts per million (sub-ppm) mass accuracy across a wide mass range. The latest breakthroughs in ToF MS instrumentation are associated with multireflecting technology, enabling the attainment of a resolving power of 10 5 and beyond. This increased resolution brings about a significant enhancement in mass measurement precision and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lack of routine gas phase separations within MSI, an ultrahigh mass resolving power exceeding 240 k is often required throughout a detected mass range (e.g., from m/z 150 to 1500). 13 This is especially true when considering MSI-based lipidomics where high levels of biomolecular complexity are present; in MALDI-MSI experiments, mass splits as low as 1.79 mDa ( 12 C 2 13 C 1 14 N 1 vs 1 H 3 16 O 3 ) in negative ion mode have been observed for a murine brain tissue sample. 14 While time-of-flight and Orbitrap studies have demonstrated the ultrahigh mass resolving power required for MSI lipidomics, 15,16 the vast majority of nano-DESI and MALDI-MSI analyses do not use sufficient resolving power to resolve common lipid ambiguities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 This is especially true when considering MSI-based lipidomics where high levels of biomolecular complexity are present; in MALDI-MSI experiments, mass splits as low as 1.79 mDa ( 12 C 2 13 C 1 14 N 1 vs 1 H 3 16 O 3 ) in negative ion mode have been observed for a murine brain tissue sample. 14 While time-of-flight and Orbitrap studies have demonstrated the ultrahigh mass resolving power required for MSI lipidomics, 15,16 the vast majority of nano-DESI and MALDI-MSI analyses do not use sufficient resolving power to resolve common lipid ambiguities. Therefore, complexity remains from ambiguous annotations based on the species detected.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation